Perkembangan Rumah Lanting di Kelurahan Seberang Mesjid Kecamatan Banjarmasin Tengah Kota Banjarmasin Tahun 2015-2020 - Sofiyani, Windi Indah; Mansyur, Mansyur; Effendi, Rusdi (Prabayaksa: Journal of History Education, 2023)
Lanting house is a floating house located on the river. Its existence as a place to live began to decrease since the people chose to move home to the mainland, which was caused by several factors, such as the construction of houses on land, and moving houses because of work. The purpose of this writing is to find out the background of lanting houses, the development of lanting houses, and the preservation of lanting houses in Seberang Mesjid Neighborhoods in 2015-2020. The benefits obtained in this study are to provide information and insight into typical Banjar houses, namely lanting houses located in Seberang Mesjid Neighborhoods as an effort to preserve traditional culture in typical Banjar house architecture. The methods used in this study are historical methods, namely heuristics, criticism, interpretation and historiography. The results showed that currently the culture of lanting houses in Banjarmasin City began to change due to changes in orientation patterns from rivers to land and the limited availability of building materials that were difficult to obtain, making the development of lanting houses in Seberang Mesjid Neighborhoods decreased. The relevant government also clarified the legal status of lanting houses in order to facilitate efforts to maintain lanting houses and be able to carry out empowerment. The conclusion of this study is that lanting houses need to be preserved with the aim of developing river-based tourism in Banjarmasin City, where lanting houses are one point of 18 tourism development points in the northern zone of Banjarmasin City.